(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This research includes synthesis and identification of new polymers that are expected having industrial applications in paint ships and dyes. These polymers were prepared from cheap and available materials such as glycerol and catechol, hydroquinone and resorcinol and using cheap catalyst in good yields. The resulting compounds were identified by FT-IR, 1H-NMR, 13C-NMR, CHN, and DSC techniques. Some physical properties of these compounds were studied